2005
DOI: 10.1063/1.2009647
|View full text |Cite
|
Sign up to set email alerts
|

Fields of accelerated sources: Born in de Sitter

Abstract: This paper deals thoroughly with the scalar and electromagnetic fields of uniformly accelerated charges in de Sitter spacetime. It gives details and makes various extensions of our Physical Review Letter from 2002. The basic properties of the classical Born solutions representing two uniformly accelerated charges in flat spacetime are first summarized. The worldlines of uniformly accelerated particles in de Sitter universe are defined and described in a number of coordinate frames, some of them being of cosmol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…Such a directional dependence was explicitly found and described for the first time in the context of the test electromagnetic field generated by a pair of uniformly accelerated point-like charges in the de Sitter background [101,108]. In particular, it was demonstrated that there always exist two special directions -those opposite to the direction from the sources -along which the radiation vanishes.…”
Section: On Studies Of Asymptotic Behaviour Of Radiative Fields In Gementioning
confidence: 94%
“…Such a directional dependence was explicitly found and described for the first time in the context of the test electromagnetic field generated by a pair of uniformly accelerated point-like charges in the de Sitter background [101,108]. In particular, it was demonstrated that there always exist two special directions -those opposite to the direction from the sources -along which the radiation vanishes.…”
Section: On Studies Of Asymptotic Behaviour Of Radiative Fields In Gementioning
confidence: 94%
“…The classical problem of inertial and accelerated charges in various charts of dS spacetime has been examined in refs [2,3]. For comoving observers situated at fixed comoving distance, which have p cons = 0, the electric field is purely radial and there is no magnetic field, signaling thus the absence of radiation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional ways to do it are the method of Green function and the conformal mapping method [10].…”
Section: Discussionmentioning
confidence: 99%